2008
DOI: 10.1002/bit.21622
|View full text |Cite
|
Sign up to set email alerts
|

Lentiviruses inefficiently incorporate human parainfluenza type 3 envelope proteins

Abstract: We have previously shown that the envelope glycoproteins of human parainfluenza type 3 (HPIV3), F and HN, are able to pseudotype lentiviruses, but the titers of these viruses are too low for use in clinical gene transfer. In this study we investigated the cause of these low titers. We compared the mRNA and protein expression levels of HN and F in transfected cells and in cells infected with wild-type HPIV3. Transfected cells contained similar levels of HN and F cytosolic mRNA, but fewer cell-surface HN and F p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 66 publications
0
2
0
Order By: Relevance
“…We used a VSV-based vector system to study cellular entry of HAL and NAL-bearing particles. VSV pseudotypes allow convenient analysis of entry driven by diverse glycoproteins [28,31,61], although one should keep in mind that due to differences in particle shape and efficiency of glycoprotein incorporation pseudotypes might not adequately mirror all aspects of cellular entry of authentic viruses [62,63]. We found that cell lines frequently used for FLUAV propagation were not susceptible to transduction by HAL and NAL bearing particles, which is in agreement with the finding that replacement of batFLUAV-HAL and -NAL by their FLUAV counterparts is required for spread of batFLUAV in the cell lines studied so far [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…We used a VSV-based vector system to study cellular entry of HAL and NAL-bearing particles. VSV pseudotypes allow convenient analysis of entry driven by diverse glycoproteins [28,31,61], although one should keep in mind that due to differences in particle shape and efficiency of glycoprotein incorporation pseudotypes might not adequately mirror all aspects of cellular entry of authentic viruses [62,63]. We found that cell lines frequently used for FLUAV propagation were not susceptible to transduction by HAL and NAL bearing particles, which is in agreement with the finding that replacement of batFLUAV-HAL and -NAL by their FLUAV counterparts is required for spread of batFLUAV in the cell lines studied so far [18,19].…”
Section: Discussionmentioning
confidence: 99%
“…Codon optimization was previously used to optimize production of pseudotyped LVVs and γ-RVVs, e.g., with Spike protein from SARS-CoV-1 [ 32 ], parainfluenza type 3 envelope proteins [ 33 ], and a truncated HIV-Env [ 34 ]. In striking contrast, Zucchelli et al observed impaired functionality of codon-optimized RD114-TR, another envelope protein derived from a γ-retrovirus that is commonly used for pseudotyping [ 20 ].…”
Section: Discussionmentioning
confidence: 99%